2021
DOI: 10.1136/bmjopen-2020-046286
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices regarding health self-management among patients with osteogenesis imperfecta in China: an online cross-sectional survey

Abstract: ObjectivesAssessing the knowledge, attitude and practices (KAP) regarding health self-management among patients with osteogenesis imperfecta (OI) in China.DesignAn online cross-sectional survey.SettingA structured questionnaire was distributed online through China-Dolls Center for Rare Disorders (CCRD), a non-governmental charity in China.ParticipantsParticipants were all patients with OI from CCRD. After stratified sampling according to the economic level of residential city, 901 patients were proportionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Another study in China, however, revealed that 59% of osteogenesis imperfecta patients were aware of the significance and process of bone mineral density measurement. [ 29 ] This finding raised concerns about the level of awareness and understanding regarding the significance of monitoring for effective osteoporosis management. Regular monitoring allows for timely assessment of treatment effectiveness and potential adjustments, which are crucial for optimal management of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in China, however, revealed that 59% of osteogenesis imperfecta patients were aware of the significance and process of bone mineral density measurement. [ 29 ] This finding raised concerns about the level of awareness and understanding regarding the significance of monitoring for effective osteoporosis management. Regular monitoring allows for timely assessment of treatment effectiveness and potential adjustments, which are crucial for optimal management of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The varieties included in the catalogue of drugs for national basic medical insurance should be those that guarantee the safety and effectiveness of drug use and safeguard basic medical needs. Self-management behavior plays a vital role in the health of residents [ 62 ]. Changing the residents’ perception of self-medication, focusing on the safety and efficacy of OTC options, and promoting and valuing health education and the safe use of OTC drugs can contribute to the effective and efficient development of medical care.…”
Section: Discussionmentioning
confidence: 99%
“…OI is an extremely rare disease, and both doctors and patients might have relatively insufficient knowledge of disease treatment. As a result, the patients were diagnosed with OI but did not receive timely treatment until repeated fractures and even bone deformities occurred ( 32 ).…”
Section: Discussionmentioning
confidence: 99%